Rethinking Educational Research Involving Students with Disabilities - Precious Muzite; Velisiwe Gasa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: This paper investigates the decolonisation of educational research concerning students with disabilities. Aims: The primary aim was to validate and interpret these students' lived experiences, challenging established dominant epistemologies in disability studies. Methods: A radical near-experience methodology, which emphasises participant-driven storytelling within their contextual realities, was employed as a qualitative research design. Twenty youths, aged 16 to 24, with either physical or learning disabilities, enrolled at five TVET Colleges, or Technical and Vocational Education and Training Colleges, in Gauteng, South Africa, engaged in storytelling exercises tailored to their abilities. Results: The storytelling exercises revealed key themes, including identity affirmation, systemic challenges, and agency. Findings indicate that conventional disability research often marginalises students' voices, perpetuating stereotypes and failing to enact meaningful policy changes. For instance, participants expressed feelings of empowerment and recognition through their narratives. Conclusion: This research holds significant implications for policymakers, highlighting the need for inclusive education studies that genuinely reflect the experiences of students with disabilities. Disability advocates can utilise these narratives to promote redefined identities and rights. Scholars can incorporate decolonial methodologies into their work, fostering a nuanced understanding of disability relevant to the global South. Additionally, practitioners in human services can leverage these insights to design supportive programs that encourage self-advocacy and positive identity formation. By prioritising the voices and experiences of individuals with disabilities, this study underscores the transformative potential of inclusive educational practices.